2018
DOI: 10.4194/1303-2712-v18_5_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Shardara reservoir is located in southernmost Kazakhstan, in the zone of intensive farming and industrial development. Zooplankton and basic parameters of the environment have been studied in the summer of 2015. Zooplankton was represented by 60 species. The average abundance of the community amounted to 92.9 thous. specimens m -3 , with biomass of 966.0 mg m -3 . Copepods and rotifers dominated. The Shannon index values were equal to 2.24 bit specimen -1 and 1.23 bit mg -1 . The average individual mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The predominantly negative relationships between the Shannon Bi index and an average individual mass of a specimen indicated that zooplankton communities with small-sized species were more diverse than communities with large-sized species. These results were consistent with previously obtained data on negative relationships between an average individual mass of a specimen or an average cell volume and the diversity of phytoplankton communities [30] and zooplankton [25,26].…”
Section: Water Areasupporting
confidence: 93%
See 2 more Smart Citations
“…The predominantly negative relationships between the Shannon Bi index and an average individual mass of a specimen indicated that zooplankton communities with small-sized species were more diverse than communities with large-sized species. These results were consistent with previously obtained data on negative relationships between an average individual mass of a specimen or an average cell volume and the diversity of phytoplankton communities [30] and zooplankton [25,26].…”
Section: Water Areasupporting
confidence: 93%
“…Correlation analysis showed that there is a statistically significant strong positive relationship between ∆-Shannon and W-statistics of Clark (Table 8), which we recorded earlier in the study of plankton communities of various water bodies of Kazakhstan [23][24][25][26]. This close relationship is explained by the fact that the calculation of both variables is based on the same principles-the ratio of species in terms of abundance and biomass.…”
Section: Water Areasupporting
confidence: 62%
See 1 more Smart Citation
“…Statistical maps were used in earlier environmental studies Krupa, Barinova, Amirgaliyev, et al, 2017b;Krupa, Barinova, Assylbekova, et al, 2018c;Krupa, Barinova, Isbekov, et al, 2018a;Krupa, Barinova, Ponamareva, et al, 2018b;Krupa, Barinova, Tsoy, et al, 2017a). Within the framework of the present study, however, overlaying of statistical maps on the contours of waterbodies for the first time made data visualization easier for analysis purposes, compared to previous methods.…”
Section: Discussionmentioning
confidence: 99%
“…T he Shardara reservoir is the largest artificial reservoir in Southern Kazakhstan, created to meet irrigation and hydropower needs by regulating the runoff of the Syr Darya River. The Shardara reservoir is one of the largest fisheries in Kazakhstan; therefore, the study of the diversity of its microbiome, phytoplankton, and zooplankton is one of the significant tasks of ecological monitoring in the region (1,2).…”
mentioning
confidence: 99%